Metabolic Syndrome and Physical Performance: The Moderating Role of Cognition among Middle-to-Older-Aged Adults. (10th February 2021) - Ogawa, Elisa F.; Leritz, Elizabeth; McGlinchey, Regina; Milberg, William; Bean, Jonathan F.
Abstract: Objective: Mobility limitation and cognitive decline are related. Metabolic syndrome (MetS), the clustering of three or more cardiovascular risk factors, is associated with decline in both mobility and cognition. However, the interrelationship among MetS, mobility, and cognition is unknown. This study investigated a proposed pathway where cognition moderates the relationship between MetS and Mobility. Method: Adults ages 45–90 years were recruited. MetS risk factors and mobility performance (Short Physical Performance Battery (SPPB) and gait speed) were evaluated. Cognition was assessed using a comprehensive neuropsychological battery. A factor analysis of neuropsychological test scores yielded three factors: executive function, explicit memory, and semantic/contextual memory. Multivariable linear regression models were used to examine the relationship among MetS, mobility, and cognition. Results: Of the 74 participants (average age 61 ± 9 years; 41% female; 69% White), 27 (36%) participants manifested MetS. Mean SPPB score was 10.9 ± 1.2 out of 12 and gait speed was 1.0 ± 0.2 m/s. There were no statistically significant differences in mobility by MetS status. However, increase in any one of the MetS risk factors was associated with decreased mobility performance after adjusting for age and gender (SPPB score: β (SE) -.17 (0.08), p < .05; gait speed: -.03 (.01), p < .01). Further adjusting for cognitive factors (SPPB score: explicit memory .31 (.14), p = .03; executive function 0.45 (0.13), p < .01; gait speed: explicit memory 0.04 (0.02), p = .03; executive function 0.06 (0.02), p < .01) moderated the relationships between number of metabolic risk factors and mobility. Conclusion: The relationship between metabolic risk factors and mobility may be moderated by cognitive performance, specifically through executive function and explicit memory.